Isolation and morphological and molecular characterization of waterborne free-living amoebae: Evidence of potentially pathogenic Acanthamoeba and Vahlkampfiidae in Assiut, Upper Egypt - Nageeb, Martina M.; Eldeek, Hanan E. M.; Attia, Rasha A. H.; Sakla, Atef A.; Alkhalil, Samia S.; Farrag, Haiam Mohamed Mahmoud (PLOS ONE, 2022)
Free-living amoebae (FLA) are gaining attention due to the increasing number of related grave central nervous system (CNS) and sight-threatening eye infections and their role as Trojan horses for many bacteria and viruses. This study was conducted in Assiut City, Egypt to detect the presence of FLA in different water sources using morphological and molecular approaches and determine their potential pathogenicity. A total of 188 water samples (100 tap, 80 tank, and 8 swimming pool samples) were collected, cultivated on non-nutrient agar seeded with Escherichia coli, and inspected for FLA. Thermo- and osmo-tolerance assays were performed to determine their pathogenicity. Polymerase chain reaction and sequence analysis were performed to confirm the identification and analyze the genotype. Overall, 52 samples (27.7%) were positive for FLA. Of these, 20.7% were identified as Acanthamoeba, 1.6% as Vahlkampfiidae, and 5.3% as mixed Acanthamoeba and Vahlkampfiidae. Seven species of Acanthamoeba were recognized, of which A. triangularis, A. polyphaga, A. lenticulata, and A. culbertsoni are thermo- and osmo-tolerant, and A. astronyxis, A. comandoni, and A. echinulata are non-thermo- and non-osmo-tolerant. The phylogeny analysis revealed T4 and T7 genotypes. Among Vahlkampfiids, 61.5% were identified as thermo- and osmo-tolerant Vahlkampfia, and 30.8% were identified as non-pathogenic Naegleria. One isolate (7.7%) was identified as potentially pathogenic Allovahlkampfia, as confirmed by sequencing. This is the first report documenting the occurrence and phylogeny of waterborne FLA (Acanthamoeba/Vahlkampfiidae) in Assiut, Egypt. The presence of potentially pathogenic FLA highlights the possible health hazards and the need for preventive measures.